Analysis of press photography in the 2024 presidential elections in Mexico - Rivera Aguilera, Luis Roberto; Rivera Aguilera, Julio César; Castro Marmolejo, Juan Manuel (Revista General de Información y Documentación, 2025)
The research contextualizes the role that press photography plays today, as an important and transcendent element that records and documents social, cultural and political processes. The study was carried out with a quantitative methodological approach. Twelve digital newspapers were selected for data collection and analysis, six nationally and six internationally; A semi-structured instrument composed of 12 variables was used, with which we sought to identify attributes, characteristics and distinctive features of digital images, with the purpose of analyzing the use of press photography during the candidates' campaign stage, Claudia Sheinbaum , Xóchitl Gálvez and Jorge Álvarez Máynez in the 2024 presidential election in Mexico, in the period defined by the National Electoral Institute, which spanned from March 1 to March 31 May. In the development of the investigation, the analysis of images published in different journalistic articles was carried out, with the purpose of identifying the candidate shown in them. The results of the study expose different findings, for example, trends in the use of the image in campaigns, photographs per newspaper, types of shots, photography agencies, publication day, photographers, among others, which account for the use of the image in the electoral process and contrast the number of photographs published with respect to the result of the presidential election. The conclusions of the study confirm what was achieved in the election where the candidate Claudia Sheinbaum was the winner of the process.
Keywords: Press photography; Presidential candidates; Elections - Mexico; Photojournalism; Advertising image